Modeling of the stress-strain relationship for specimens made of S355J0 steel subjected to bending block loading with mean load - R. Pawliczek; C.T Lachowicz (Fracture and Structural Integrity)
The paper presents results of calculation for modelling of the stressstrain relationship in the case of block loads with mean load value. A model, based on the stable hysteresis loops, was assumed and modified to use for block loading analysis. For stress history calculation, the proposed model and two other constitutive models were used. Results of fatigue test of specimens made of S355J0 steel subjected to bending block loading with mean load value are presented and used to verify the proposed model. In the tests, the mean load was increased and decreased in subsequent blocks. The changes of strain recorded during the tests shown in the paper indicate a different behavior of the material. Damage accumulation degree for block sequence was used to compare the results of calculations. It was shown, that stress history parameters (stress amplitude and mean stress value in this case) are similar for all investigated models.